Exploring migrant entrepreneurship and innovation in ultraperipheral regions: An investigation on opportunity and necessity-driven entrepreneurship - José António Porfírio; José Augusto Felício; Ricardo M. Rodrigues; Tiago Carrilho (Journal of Innovation & Knowledge (JIK), 2024)
Migrant entrepreneurship involves the indigenous population and migrant communities, exerting a profound influence on the host country or region. This phenomenon is particularly relevant in ultraperipheral areas, as in this research exemplified by the Autonomous Region of Madeira (Madeira), which recently witnessed an intensification of migrant inflow, many originating from countries with a deep historical connection to the region. This research characterizes the entrepreneurial migrant community to discern factors that may contribute to formulating and enhancing political-social policies to foster entrepreneurship success, broadly relevant to generating wealth but of particular importance in facilitating migrants' integration. The analysis focuses on understanding the motivations that drive entrepreneurial initiatives among migrants, recognizing the predominance of necessity-driven entrepreneurs, and that migrant entrepreneurs often take advantage of historical and familial ties to the region to overcome the obstacles specific to migrants.
Keywords: L26; 650; Migrant entrepreneurship; Necessity-driven entrepreneurship; Opportunity-driven entrepreneurship; Ultraperipheral regions; fsQCA